PEMATAHAN DORMANSI BENIH SENGON BUTO (Enterolobium cyclocarpum) MENGGUNAKAN ASAM KLORIDA (HCl) - Eka Suzanna; Farida Aryani; Yukiman Armadi; Neti Kesumawati (Agriculture, 2026)
Sengon Buto Seeds (Enterolobium cyclocarpum) have hard and thick seeds making it difficult to germinate. Efforts to break sengon buto seed dormancy can be done by using hard acids, one of them is hydrochloric acid (HCl), which can soften the hard surface of the seed coat. This study aims to obtain the concentration and the soaking time of hydrochloric acid in accelerating the breaking of dormancy of sengon buto seeds. The design used in this study was a completely randomized design (CRD) factorial pattern with 3 replications. The first factor studied was the concentration of hydrochloric acid (HCl) (K) consisting of 3 levels, namely: K1 = 1% (1 ml/l water), K2 = 2% (2 ml/l water) and K3 = 3% (3 ml/l water). The second factor is soaking time (L) consisting of 3 levels, namely: L1 = 6 hours, L2 = 12 hours and L3 = 18 hours. The parameters studied were germination capacity, germination speed, germination uniformity, vigor index and seedling dry weight. The results showed that the concentration of hydrochloric acid (HCl) had a very significant effect on the germination capacity and the germination uniformity of sengon buto seeds, had a significant effect on the germination speed and seedling dry weight. However, it did not have a significant effect on vigor index. The hydrochloric acid concentration of 3% (3 ml/l water) could break the seed dormancy and increase the germination. The soaking time did significantly affect the germination capacity and the germination uniformity. However, it did not have a significant effect on germination speed, vigor index, and seedling dry weight of sengon buto seeds. The best soaking time for sengon buto seeds is 12 hours to break their dormancy. There was interaction between HCl concentration and soaking time on germination uniformity variables. Treatment with hydrochloric acid concentrations of 3% (3 ml/l water) and 12-hour soaking time gave a maximum germination uniformity of 44%. Key words: dormancy, hydrochloric acid, seed